Validation of educational material for the care of people with intestinal stoma - Julliana Fernandes de Sena; Isabelle Pereira da Silva; Silvia Kalyma Paiva Lucena; Adriana Catarina de Souza Oliveira; Isabelle Katherinne Fernandes Costa (Universidade de São Paulo, 2020)
Abstract Objective: to validate an educational booklet for people with intestinal stoma as a technological resource in the teaching of self-care. Method: a methodological research for the construction and validation of an educational booklet by nine expert judges and 25 people with stomas. The agreement index of at least 80% was considered to guarantee the validation of the material. Results: regarding the objectives of the booklet, all the judges evaluated the items as "adequate" or "totally adequate", with a content validity index of 1.00. Regarding the structure and presentation of the booklet, the total index was 0.84. Regarding relevance, the total was 0.97 and the general index of the educational booklet was 0.89, confirming the validation with the judges. All items of the organization, writing style, appearance and motivation of the material were considered as validated by the target audience, reaching a total agreement index of 0.99. Conclusion: in the context of health education, the booklet was considered valid and suitable for the care of people with intestinal stoma, and can be used in teaching, research, extension and care for people with intestinal stoma.